Complexos de rutênio contendo lapachol e lausona: síntese, caracterização e suas propriedades quimioterapêuticas - Oliveira, Katia Mara de (2014)
The present work focuses on the synthesis and characterization of new ruthenium complexes containing the naphthoquinones lapachol and lawsone, due to the interesting biological properties exhibited by them. Complexes of general formula [Ru(L)(dppb)(N-N)]PF6, trans-[Ru(L)(PPh3)2(N-N)] PF6 and cis-[Ru(PPh3)2(lap)2] where L refers to the ligands lapachol (lap) or lawsone (lau), N-N corresponds to 2,2'-bipyridine, 4,4'- dimethyl-2,2'-bipyridine, 4,4'-dimethoxy-2,2'-bipyridine and 1,10- phenanthroline, dppb = 1,4-bis(diphenylphosphino)butane and PPh3 = triphenylphosphine. All synthesized compounds were characterized by molar conductivity, elemental analysis, infrared absorption spectroscopy, UV-visible absorption spectroscopy, 31P{1H}, 1H and 13C{1H} nuclear magnetic resonance, cyclic and differential pulse voltammetry, and for some complexes, by X-ray crystallography. The complexes were evaluated with respect their cytotoxic activity in tumor lines cell MCF-7 (breast adenocarcinoma) and L929 (normal mouse fibroblast), which showed very promising results with IC50 values in the range 0.12 to 1.11 μM. In addition, the complexes proved to be more active than the reference drug, cisplatin, which has IC50 μM to 13.98 MCF-7 lineage and 20.14 uM to L929. For the purpose of elucidating the possible mechanism of complex action, studies of interaction with DNA and with bovine serum albumin (BSA) were performed.